2021
DOI: 10.1186/s13027-021-00400-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of systemic immune-inflammation index (SII), early warning score (ANDC) and prognostic nutritional index (PNI) in hospitalized patients with malignancy, and their influence on mortality from COVID-19

Abstract: Introduction We evaluated several biological indicators based on inflammation and/or nutritional status, such as systemic immune-inflammation index (SII), early warning score (ANDC) and prognostic nutritional index (PNI) in hospitalized COVID-19 patients with and without malignancies for a prognostic significance. Methodology This is a retrospective and observational study on 186 patients with SARS-CoV-2, who were diagnosed with COVID-19 by real-ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 39 publications
(42 reference statements)
0
13
0
Order By: Relevance
“…Indicators of a systemic inflammatory response, such as derived neutrophil to lymphocyte ratio (dNLR), monocyte to lymphocyte ratio (MLR), platelet to lymphocyte ratio (PLR), and systemic inflammatory response index (SIRI) have facilitated mortality prediction in COVID-19 patients ( 6 , 7 ). In addition, a high systemic immune-inflammation index (SII) and neutrophil to lymphocyte ratio (NLR) are also biomarkers that influence COVID-19-related mortality ( 8 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Indicators of a systemic inflammatory response, such as derived neutrophil to lymphocyte ratio (dNLR), monocyte to lymphocyte ratio (MLR), platelet to lymphocyte ratio (PLR), and systemic inflammatory response index (SIRI) have facilitated mortality prediction in COVID-19 patients ( 6 , 7 ). In addition, a high systemic immune-inflammation index (SII) and neutrophil to lymphocyte ratio (NLR) are also biomarkers that influence COVID-19-related mortality ( 8 10 ).…”
Section: Introductionmentioning
confidence: 99%
“… NLR predicts mortality better than age, LDH, CRP, and lymphocyte levels, suggesting it may be the best predictive parameter (p<0.05). Bilge et al 2021 66 Cancers n=75 No cancers n=111 7.02 5.52 NS - - - - There are no significant differences in NLR value between the two compared groups in this study. Waris et al 2021 90 Mild n=52 Moderate n=24 Severe n=9 Critical n=16 Mild=2.7 Moderate=4.95 Severe=5.11 Critical=6.87 <0.001 - - - - NLR may be helpful for clinicians to identify potentially severe cases at early stages, initiate effective management in time, and conduct early triage which may reduce the overall mortality of COVID-19 patients.…”
Section: Introductionmentioning
confidence: 50%
“…The researchers emphasize the need for a further analysis of this parameter in the evaluation of patients’ condition ( Table 3 ). 66 , 67 , 73 , 86 …”
Section: Introductionmentioning
confidence: 99%
“…This score, developed with mathematical and statistical calculations, was calculated with the formula (1.14 × age -20) (years) + 1.63 × neutrophil/lymphocyte ratio + 5.00 × D-dimer (mg/L) + 0.14 × C-reactive protein (mg/L) (13). Bilge et al confirmed in their study that ANDC is an independent biomarker (14).…”
Section: Dear Editormentioning
confidence: 77%